Beyrut vilâyeti - Temîmî, Mehmet Refik, 1887/88-1956/57. (Beyrut)
2 cilt (1. c. [1] yaprak harita, [2], 456 sayfa, [26] yaprak resim, harita ; 2. c. 604 sayfa, [19] yaprak resim, çizim, harita, plan, tablo